Pengaruh Antimicrobial Dressing terhadap Proses Penyembuhan Luka Pada Pasien Post Debridement Ulkus Kaki Diabetik di Ruang Telukjambe RSUD Karawang - Daruquthni, Daruquthni; Rakhmawati, Arifah (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Patients who suffer from diabetes mellitus for more than 5 years are twice as likely to develop diabetic ulcers.The prevalence of diabetic foot ulcer sufferers in Indonesia is 15% of all diabetes mellitus sufferers, 30% have amputations and 32% mortality. Diabetes mellitus sufferers are very vulnerable to amputation due to the chronic condition of the disease and a greater risk of complications. The purpose of this writing is to determine the effect of Antimicrobial Dressing on the wound healing process in post-debridement patients with Diabetic Foot Ulcers in the Telukjambe Room, Karawang Regional Hospital. The research method used was quasi experiment. A quasi experiment is defined as an experiment with treatments, effectiveness measures, and experimental units, but does not use random allocation as a comparison to infer changes caused by the treatment. The treatment in this study was antimocrobal dressing. Research results: The average time for wound healing in the group using antimicrobials was 4 days with a standard deviation of 3,090 days. Statistical test results obtained a p value of 0.09 (>0.05), on the 3rd day the p value was 0.63 (>0.05) and on the 6th day the p value was 0.18 (>0.05). Conclusions and RecommendationsThe results of the study show that 13 respondents (25%) received antimicrobial dressing treatment for 1-3 days with a moderate wound healing process compared to 10 respondents (19.2%) who received antimicrobial dressing treatment for > 6 days. From the Chi Square statistical test, it was found that the p value was 0.002 < 0.05 α, so reject Ho and accept Ha, it can be concluded that there is a relationship between the effect of antimicrobial dressings on the condition of the wounds on the feet of patients suffering from diabetic ulcers in the Telukjambe room. Keywords: Antimocrobal Dressing, Diabetic Foot Ulcers, Post Debridement. ABSTRAK Pasien yang menderita diabetes melitus lebih dari 5 tahun dua kali lebih berisiko terjadi ulkus diabetikum. Prevalensi penderita ulkus kaki diabetik di Indonesia sebanyak 15% dari seluruh penderita diabetes melitus, 30% terjadi amputasi dan 32% mortalitas. Penderita diabetes melitus sangat rentan mengalami amputasi disebabkan kondisi penyakit yang kronik dan risiko komplikasi yang lebih besar. Tujuan Penulis mengetahui pengaruh Antimicrobial Dressing terhadap proses penyembuhan luka pada pasien post debridement Ulkus Kaki Diabetik di Ruang Telukjambe RSUD Karawang. Metode penelitian yang digunakan adalah quasy experiment. Quasy eksperiment didefinisikan sebagai eksperimen dengan perlakuan, pengukuran keefektifan, dan unit percobaan, tetapi tidak menggunakan alokasi acak sebagai perbandingan untuk menyimpulkan perubahan yang disebabkan oleh perlakuan. Perlakuan dalam penelitian ini adalah Antimocrobal dressing. Hasil Penelitian rata-rata waktu penyembuhan luka  pada kelompok yang menggunakan  antimicrobial adalah 4 hari  dengan standar deviasi 3.090 hari Hasil uji statistic didapatkan p value 0,09 (>0.05) hari ke 3 p value 0.63 (>0.05) dan pada hari ke 6 di dapatkan p value 0,18 (>0.05). Kesimpulan dan Saran Hasil penelitian menunjukan responden dengan perawatan antimicrobial dresing selama 1-3 hari  dengan proses penyembuhan luka sedang sebanayak 13 responden (25%)  lebih besar  dibanding dengan responden dengan perawatan antimicrobial dresing selama >6  hari  dengan proses penyembuhan luka kurang dengan jumlah responden 10 orang (19.2%). Dari uji statistik Chi Square didapat p Value 0,002 < 0,05 α jadi tolak Ho dan terima Ha, maka dapat disimpulkan bahwa adaHubungan Pengaruh Antimicrobial Dressing Terhadap Kondisi Luka Pada Kaki Pasien Penderita Ulkus Diabetikum Di Ruang Telukjambe. Kata Kunci: Antimocrobal Dressing, Ulkus Kaki Diabetik, Post Debridment